New continuous recycling technology for vulcanized rubbers - Mouri M; Fukumori K; Honda H; Matsushita M; Nakashima K; Okamoto H; Owaki M; Sato N; Suzuki Y (Abstracts of Meeting Papers: 155th Meeting (Spring 99) of the Rubber Division American Chemical Society Chicago, Illinois April 13-16, 1999. p805)
A continuous devulcanization technology for vulcanized rubbers has been developed with the shear flow stage reactor. In this process, the breakages of carbon-sulfur (C-S) crosslinking points occur selectively under the controls of shear stress, reaction temperature and internal pressure in a modular screw type of the reactor. The obtained devulcanized rubber is composed of two (sol and gel) components. The sol component corresponds to linear polymer chains, and its average molecular weight is nearly equal to that of originally compounded rubber. The gel component corresponds to loosely crosslinked network chain, and its effective network chain density is evaluated to be about one twentieth of that for the vulcanized rubber. The devulcanized rubber can be revulcanized by conventional curing procedures with an accelerated sulfur vulcanization system, and be applied to practical forming processes. The revulcanized rubber exhibits excellent mechanical properties nearly equal to those of vulcanized new rubber.
Source Year: 1999
Keywords: Recycling; Vulcanized rubber